Heatline visualization of MHD natural convection in an inclined wavy open porous cavity filled with a nanofluid with a local heater - Bondareva, Nadezhda S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2016)
Numerical study of free convection in an inclined wavy open porous cavity filled with a nanofluid under an influence of the uniform magnetic field in the presence of right bottom corner heater of the constant temperature has been carried out. The domain of interest is a tilted tall cavity with aspect ratio 4 having left isothermal wavy wall and open top boundary. A heat source of constant temperature is located at the right bottom corner. Heatline visualization technique is applied to see the heat transport way. Governing equations formulated on the basis of Darcy-Boussinesq approximation with a single-phase nanofluid model have been solved by means of finite difference method. The effects of the Hartmann number, inclination angles of the cavity and magnetic field on the heat transfer and fluid flow at Ra = 1000 have been shown in terms of streamlines, heatlines, isotherms, average Nusselt number and fluid flow rate. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Open wavy porous cavity; Inclination; MHD free convection; Nanofluid; Corner heater; Heatlines